The long non-coding RNA GAS5 contributes to the suppression of inflammatory responses by inhibiting NF-κB activity - Curci, Debora; Stankovic, Biljana; Kotur, Nikola; Pugnetti, Letizia; Gasic, Vladimir; Romano, Maurizio; Zukic, Branka; Decorti, Giuliana; Stocco, Gabriele; Lucafò, Marianna; Pavlovic, Sonja (Frontiers in Pharmacology, 2024)
Nuclear factor kappa B (NF-κB) is key in regulating immune and inflammatory responses. Glucocorticoid drugs (GC) act through the glucocorticoid receptor (GR) as immunosuppressant also in pediatric patients inhibiting NF-κB activity. The long non-coding RNA GAS5 interacts with GR by competing with DNA glucocorticoid response elements for binding to the GR. Still, no data on the impact of GAS5 on GR-dependent inhibition of NF-κB activity have been published. Our study highlighted elevated DNA binding activity of NF-κB, particularly its subunit, p65, in HeLa cells overexpressing GAS5. Through RNA-immunoprecipitation assay, we demonstrated that GAS5 interacts with p65, causing a downregulation of NF-κB target genes (TNF-α, and NR3C1) in GAS5 overexpressing cells. Furthermore, western blot analysis indicated reduced p-p65/pan-p65 levels and increased IκB, implying that GAS5 may function as a negative regulator of the NF-κB signaling pathway. GC treatment reduced the ability of the transcription factor NF-κB to bind DNA in HeLa cells overexpressing GAS5. GC-related increase of IκB levels was higher in HeLa cells overexpressing GAS5 . This confirms that GAS5 may play a regulatory role in modulating the interaction between GCs and NF-κB. In conclusion, our study showed that GAS5 presents distinct modulatory roles on the NF-κB pathway under basal and GC treatment conditions: GAS5 increases NF-κB DNA binding activity in non-treated cells while decreasing it in GC-treated cells. These findings provide new insight into the complex regulation between GAS5, NF-κB, and GCs and maybe useful to develop strategies for personalization of therapy in particular for pediatric patients.